Mapping The Knowledge Domain of Metaverse The New Marketing Universe: A Bibliometric Analysis - Monika, Eilen; Setiawan, Adi; Triasnita Miranda, Iges; Monica, Tasya; Ayu Santika, Widhea; Chalirafi, Chalirafi (International Journal of Engineering, Science and Information Technology, 2023)
“Metaverse” is the idea of a shared virtual environment that is “parallelized” to the real world thanks to advances in technology. The metaverse world is currently not only used as a platform for playing games but has also been used as a place for doing business. The purpose of this research is to identify articles that study the metaverse in marketing and provide an overview of the Metaverse knowledge domain as a new marketing world and to show and explain the research mapping. This mapping will help researchers explore and develop research related to the metaverse as a new marketing world landscape. Marketing is a promotional activity that can attract consumers to increase sales. Metaverse is a virtual universe that imitates real world procedures. In this 3D virtual environment, users can carry out activities in the digital world like in the real world, as is done with the Gucci brand which uses the metaverse as a marketing medium based on blockchain TheSandbox. This will have a major impact on how companies implement marketing in the future and how people communicate with each other. In Industry 5.0, metaverse has entered the world of marketing and has begun to be used by several companies. So, metaverse becomes a new world in marketing. This research uses qualitative methods with bibliometric techniques by utilizing Visualization of Similarities (Vosviewers) as an application. By entering keywords such as Metaverse; Metaverse marketing; Digital Marketing; New Marketing Universe; Gen z to search for articles via Publish or Perish with a total of 940 articles which were then processed using VosViewers. The results of the analysis found scientific mapping and possible future studies regarding the metaverse as a new marketing world that can be used as variable recommendations for future researchers as a reference for subsequent articles.